Experience of Initial Symptoms of Breast Cancer and Triggers for Action in Ethiopia - Timothy D. Dye; Solomon Bogale; Claire Hobden; Yared Tilahun; Teshome Deressa; Anne Reeler (International Journal of Breast Cancer)
Objective. This study assessed the initial experiences, symptoms, and actions of patients in Ethiopia ultimately determined to have breast cancer. Methods. 69 participants in a comprehensive breast cancer treatment program at the main national cancer hospital in Ethiopia were interviewed using mixed qualitative and quantitative approaches. Participants’ narratives of their initial cancer experience were coded and analyzed for themes around their symptoms, time to seeking advice, triggers for action, and contextual factors. The assessment was approved by the Addis Ababa University Faculty of Medicine Institutional Review Board. Results. Nearly all women first noticed lumps, though few sought medical advice within the first year (average time to action: 1.5 years). Eventually, changes in their symptoms motivated most participants to seek advice. Most participants did not think the initial lump would be cancer, nor was a lump of any particular concern until symptoms changed. Conclusion. Given the frequency with which lumps are the first symptom noticed, raising awareness among participants that lumps should trigger medical consultation could contribute significantly to more rapid medical advice-seeking among women in Ethiopia. Primary care sites should be trained and equipped to offer evaluation of lumps so that women can be referred appropriately for assessment if needed.